Circulating PD-1+ effector memory T cells predict anti-PD-1 efficacy in advanced gastric cancer - Wang, Kongcheng; Shao, Jie; Xin, Kai; Zhang, Lianru; Liu, Baorui; Chen, Wenxiu; Liu, Qin (Frontiers in Immunology, 2025)
BackgroundAlthough standard chemotherapy combined with immunotherapy represented by programmed cell death -1(PD-1) blockade shows promise as a treatment approach for gastric cancer (GC), the drug response rates remain low. Identifying reliable biomarkers to predict patient response is urgently needed.MethodsWe collected baseline (before receiving PD-1 inhibitors) peripheral blood samples from advanced GC patients (n=54) who underwent PD-1 inhibitors and platinum drugs from January 2022 to December 2023 and investigated PD-1 expression on effector memory T (TEM) between responders and non-responders according to Response Evaluation Criteria in Solid Tumors (RECIST 1.1) guidelines by low-dose computed tomography scan evaluation. Univariate and multivariate analyses were applied to identify potential predictive biomarker for chemo-immunotherapy combinations outcomes. In vitro cytotoxicity and cytokine detection were used to demonstrate the effects of PD-1 blockade on TEM cells with different levels of PD-1 expression.ResultsThe optimal cutoff values for percentages of PD-1+ cells in TEM were 8.66%. Among advanced GC patients receiving anti-PD-1 therapy, responders exhibited a higher mean percentage of PD-1+ cells in TEM (P = 0.017) than non-responders, which were associated with longer PFS. Univariate and multivariate Cox regression analyses demonstrated that higher percentage of PD-1+ cells in TEM (HR = 0.191, 95% CI 0.065–0.560, P = 0.003) was independent protective factor in advanced GC patients receiving chemo-immunotherapy. In vitro, PD-1 blockade enhanced TEM activation, as evidenced by increased cytotoxicity and IFN-γ secretion, leading to improved anti-tumor capacity.ConclusionOur data identify a high pretreatment percentage of PD-1+ cells in TEM as a potential predictive biomarker for response to PD-1 blockade.